2018
DOI: 10.1111/1346-8138.14223
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic reconstruction of retroauricular keloid: Creating a keystone flap from the mastoid‐helix area

Abstract: Advances in aesthetic rhinoplasty using conchal cartilage grafts have led to a high occurrence of retroauricular keloids. The purpose of this study is to introduce our surgical experiences using a keystone flap in retroauricular keloids following conchal cartilage grafts. The present study is a retrospective review of patients with pathologically confirmed retroauricular keloids following conchal cartilage grafts. These cases were surgically excised and we covered the defect with a keystone flap followed by on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Our published work review showed that traditional keystone flaps showed excellent outcome in various clinical settings. 3 However, some arguments and questions inevitably arose. One of the most debated issues is the topic of wound tension.…”
Section: Discussionmentioning
confidence: 99%
“…Our published work review showed that traditional keystone flaps showed excellent outcome in various clinical settings. 3 However, some arguments and questions inevitably arose. One of the most debated issues is the topic of wound tension.…”
Section: Discussionmentioning
confidence: 99%
“…For small-to-moderate facial defects, several studies in the PubMed database primarily discussed nasal reconstructions followed by posterior auricular and medial canthal reconstructions. [68,21,22] Previous studies have described KDPIF as a single-stage reconstructive option that provided sound functional and aesthetic outcomes for nasal defects up to 2 cm in diameter, and partial thickness alar defects up to 1.5 cm in diameter. [6,7] Some of these studies have also reported that KDPIF nasal reconstructions were safe and reproducible even in the hands of inexperienced surgeons, albeit under guidance.…”
Section: Discussionmentioning
confidence: 99%
“…[3] KDPIF have grown in clinical applicability in various fields of reconstructive surgery in the past decade. [48] However, previous studies have only presented KDPIF reconstructions of facial defects in limited locations, such as large parotid defects and small-to-moderate nasal defects, but did not consider the facial aesthetic unit concept in detail. Therefore, to the best of our knowledge, we present the first report of, and a description of our experience with, relaxed skin tension line (RSTL)-oriented KDPIF reconstruction considering the facial aesthetic unit concept for the coverage of small-to-moderate facial defects in various regions.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical applications of the keystone flap have evolved over the past decade [8,9] to cover large defects in the trunk, [9,10] limbs, [1113] perineum, [14,15] and head and neck. [1619] In this study, 3 different types of modified keystone flaps were used to repair soft-tissue defects following skin tumor ablation. The selection strategy we applied for these 41 keystone flaps is feasible and has a high success rate for reconstruction.…”
Section: Discussionmentioning
confidence: 99%